(3GdLhGH GdeNJGQ Ydi eSGFd YHO GdLHGQs - (3GdbGSe Hf eMeO Hf Ydj GdefUhQ HGddg,J (B1029 (3g` s
(3ChdgG (B:s
(3bGd GdSGFd ai ebOeI eSGFdg eG jbhd YdeGA GdESdGe Zdi bhdg eTJedkG Ydi JHjjf GdMb ai cd eSCdI HCOdI bWYjI , hERGdI eG jQO Ydi Jdc GdCOdI ef GdCSFdI hGdLhGH s
(3BNQgG (B:s
(3aeG CLeYhG Ydgj EYJeO Ydjg dcf dGjSei JbdjOkG dchf ELeGYge MLI hEJHGY GdMLI hGdYed HebJVGgG dGjSei JbdjOkG HELeGY YdeGA GdESdGe hUdi Gddg Ydi SjOfG eMeO GdCejf hBdg GdCcQejf hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdahGJM HGdNW GdSejc HBNQg aGFOI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3Gdabg GdESdGejs